Temiar Religion, 1964-2012: Enchantment, Disenchantment and Re-Enchantment in Malaysia's Uplands - Benjamin, Geoffrey (NUS Press, 2014)
Half title page -- Frontispiece -- Full title page -- Copyright page -- Contents -- List of Tables and List of Figures -- Foreword -- Preface -- Orthography and Pronunciation -- Chapter 1: The Historical and Intellectual Background -- Chapter 2: The Temiars and their Religion -- Chapter 3: Temiar Religion (1967)-- Preface and Introduction -- Chapter 4: Temiar Religion (1967)--The Cosmos -- Chapter 5: Temiar Religion (1967)--Species -- Chapter 6: Temiar Religion (1967)--Souls -- Chapter 7: Temiar Religion (1967)--Spirit-mediumship -- Chapter 8: Temiar Religion (1967)--Theology -- Chapter 9: Field-report Correspondence with Edmund Leach -- Chapter 10: Temiar Mediumship in Context -- Chapter 11: Indigenous Religious Systems of the Malay Peninsula -- Chapter 12: Danger and Dialectic in Temiar Childhood -- Chapter 13: Rationalisation and Re-enchantment: Temiar Religion, 1964-94 -- Chapter 14: Temiar Religions, 1994-2012: Islam, Christianity, ʔalʉj Səlamad -- Afterword -- Appendix 1: Four accounts of H.D. Noone's work on Temiar Religion -- Appendix 2: Dance types and spirit-guide song genres -- Appendix 3: Further accounts of burial practices -- Appendix 4: Children's accounts of their dreams -- Bibliography -- Index.